PENGARUH PEMBIAYAAN TERHADAP KINERJA USAHA MIKRO DAN KECIL OLAHAN UBI KAYU DI INDONESIA - Luriana Taslim; Amzul Rifin; Siti Jahroh (Jurnal Agribisnis Indonesia, 2020)
Cassava is the most processed staple food crops in Indonesia. Processed cassava micro and small enterprises (MSEs) are responsible for most cassava value-adding process. The major obstacle to the growth of MSEs is financing—a problem of the limited source of fund. Despite the presence of government financing support to MSEs, the number of processed cassava MSEs that have involved financing is still low. This study aimed to analyze the financing impact on the performance of processed cassava MSEs and to identify which factors influence the performance of processed cassava MSEs. Cross-sectional data of the MSEs Survey conducted in 2015 by Badan Pusat Statistik and analysis tool Multiple Linear Regression was used to answer the research objectives. Results showed that financing had a positive and significant impact on processed cassava MSEs’ sales revenue, but did not have any impact on their assets. Factors that significantly affected the performance of processed cassava MSEs were working hours per day, input value, training, products marketed in town, and business belongs in chips industry.